Potensi Lepraria sp. sebagai Bioindikator Pencemaran Timbal (Pb) di Kota Bandung - Muhammad Fauzan Akbar; Iyan Robiansyah; Rina Ratnasih Irwanto (UIN Sunan Gunung Djati Bandung, 2021)
Bioindicator organism, such as lichens, a symbiosis between fungi and green algae or cyanobacteria, can be used for monitoring air pollution level in urban areas, such as Bandung City. This research aims to assess the potential of lichen Lepraria sp. as bioindicator by measuring the concentration of Pb accumulated in Lepraria sp. on the years of 2006 and 2020. Measurements in 2006 were conducted in three locations in Bandung, while measurement in 2020 was conducted only in one location, Jl. W. R. Supratman. Traffic volumes and microclimate conditions (humidity, air temperature, and light intensity) were also measured. Our results showed that Pb concentration measured in 2006 were higher along Jl. W. R. Supratman than Jl. Nyland, and the lowest is in Panatayuda Park. Traffic volume was considered to be the highest factor affecting Pb concentrations (P<0,01, r=0,823), while microclimate was found to have no effect. Measurements in 2020, which focused on Jl. W. R. Supratman, displayed a significant decrease of Pb concentrations (P<0,05). It was discovered that Pb concentrations decreased despite an increase of traffic volume. The decrease of airborne Pb concentrations, as the effect of leaded petrol ban in Indonesia, was presumed to be the cause of Pb concentration decrease in Lepraria sp. To conclude, the ability of Lepraria sp. to accumulate Pb and reflects change in airborne pollutant levels shows that Lepraria sp. has the potential to be utilized as a Pb pollution bioindicator.